Trust as a mechanism to improve organizational performance - Buenaventura-Vera, Guillermo; Gudziol, Juan Antonio (Cuadernos de Administración, 2020)
This paper designs and contrasts a relational model between the trust of collaborators in organizations and the performance of the company, mediated by the organizational commitment to learning and the commitment of employees to the company. As key objectives, a double mediation model is tested in the relationship between intra-organizational trust and the firm’s performance, through the organization’s commitment to learning and the commitment of collaborators to the company. Using a 31-item survey, the goodness of the model was evaluated with a sample of 161 individuals from different organizations in southwestern Colombia. The proposed model and its respective adjustment indexes were tested by using structural equations (SEM) modeling and the AMOS software package. The results demonstrate the empirical evidence, by statistically contrasting the model that posits the existence of relationships among the variables of the relational model. The findings made it possible to set parameters for the management of competencies and skills that contribute to the improvement of organizational performance.